User Generated Content As a Moderating Variable of the Influence of Brand Trust on Customer Satisfaction : Penelitian - Soni Suardi; Heny Herawati; Enggar Widia Ningrum; Rosita; Tabita Montolalu, Marcelitha (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This research employs a quantitative explanatory approach, relying on previous research to generate new hypotheses, modifying and proving them. The data used in this article are primary data obtained from three hundred and thirty-five COFFEE Kenagan consumers across Indonesia. The data obtained were analyzed using the Smart PLS 4.0 analysis tool. The result in this article show that the Brand Trust variable can have a positive relationship and a significant influence on Customer Satisfaction due to the P-Values ​​that are positive and below the 0.05 significance level, namely 0.012. These results mean that the better the Brand Trust, the more it will result in the product being recognized as a quality product. In addition, the User Generated Content variable can also moderate the influence of the Brand Trust variable on Consumer Satisfaction due to the same thing, namely the P-Values ​​that are positive and below the significance level. Thus, it can be concluded that the first and second hypotheses in this article can be accepted and proven.